Microbial Communities Shaped by Treatment Processes in a Drinking Water Treatment Plant and Their Contribution and Threat to Drinking Water Safety - Li, Qi; Yu, Shuili; Li, Lei; Liu, Guicai; Gu, Zhengyang; Liu, Minmin; Liu, Zhiyuan; Ye, Yubing; Xia, Qing; Ren, Liumo (Frontiers in Microbiology, 2017)
Bacteria play an important role in water purification in drinking water treatment sys-tems. On one hand, bacteria present in the untreated water may help in its purification through biodegradation of the contaminants. On the other hand, some bacteria may be human pathogens and pose a threat to consumers. The present study investigated bac-terial communities using Illumina MiSeq sequencing of 16S rRNA genes and their functions were predicted using PICRUSt in a treatment system, including the biofilms on sand filters and biological activated carbon (BAC) filters, in four months. In addi-tion, quantitative analyses of specific bacterial populations were performed by quanti-tative real-time polymerase chain reaction (qPCR). The bacterial community compo-sition of post-ozonation effluent, BAC effluent and disinfected water varied with sampling time. However, the bacterial community structures at other treatment steps were relatively stable, despite great variations of source water quality, resulting in sta-ble treatment performance. Illumina MiSeq sequencing illustrated that Proteobacteria was dominant bacterial phylum. Chlorine disinfection significantly influenced the mi-crobial community structure, while other treatment processes were synergetic. Bacteri-al communities in water and biofilms were distinct, and distinctions of bacterial com-munities also existed between different biofilms. By contrast, the functional composi-tion of biofilms on different filters were similar. Some functional genes related to pol-lutant degradation were found widely distributed throughout the treatment processes. Mycobacterium, Streptococcus and Pseudomonas, potential pathogens, were detected along the treatment processes. The distributions of Mycobacterium spp. and Legionella spp. in water and biofilms were revealed by quantitative real-time polymerase chain reaction (qPCR). Most bacteria, including pathogens, could be effectively removed by chlorine disinfection. However, some bacteria presented great resistance to chlorine. qPCRs showed that Mycobacterium could not be effectively removed by chlorine. These resistant bacteria and, especially potential pathogens should receive more atten-tion. Redundancy analysis (RDA) showed that turbidity, ammonia nitrogen and total organic carbon (TOC) exerted significant effects on community profiles. Overall, this study provides insight into variations of microbial communities in the treatment pro-cesses and aids the optimization of drinking water treatment plant design and opera-tion for public health.